2011
DOI: 10.5005/jp-journals-10005-1089
|View full text |Cite
|
Sign up to set email alerts
|

International Caries Detection and Assessment System (ICDAS): A New Concept

Abstract: Dental caries is a complex multifactorial disease of the calcified tissues of the teeth, caused by interaction of various factors including the host, agent, substrate and time as demonstrated by the Keyes circle. Detecting carious lesion at the earliest possible stage of its development is definitely helpful in appropriate treatment planning for the same. The lack of consistency among the contemporary criteria systems for detecting carious lesions limits the comparability of outcomes measured in epidemiologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
103
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(106 citation statements)
references
References 22 publications
1
103
0
2
Order By: Relevance
“…The use of the ICDAS II caries diagnostic criteria [13] in epidemiological surveys usually encounters the difficulty of not having an effective tooth drying scenario and this was solved using an approved epidemiological modification that allows merging codes 1 and 2 [14]. From the exploration with ICDAS-II criteria, the caries index was reconstructed considering all of the stages (ICDAS 2-6/C-G), or only the most advanced lesions (ICDAS 4-6/E-G) that we matched to the caries WHO criteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of the ICDAS II caries diagnostic criteria [13] in epidemiological surveys usually encounters the difficulty of not having an effective tooth drying scenario and this was solved using an approved epidemiological modification that allows merging codes 1 and 2 [14]. From the exploration with ICDAS-II criteria, the caries index was reconstructed considering all of the stages (ICDAS 2-6/C-G), or only the most advanced lesions (ICDAS 4-6/E-G) that we matched to the caries WHO criteria.…”
Section: Discussionmentioning
confidence: 99%
“…The caries status was assessed according to the ICDAS II criteria [13] with two digits; the first identifies the presence of any type of restoration or seal and the second registers the caries code for each tooth. All dental surfaces of each of the present and measurable teeth were explored: five surfaces for the premolar and molar teeth and four for the incisors and canines.…”
Section: Caries Diagnosis Criteriamentioning
confidence: 99%
“…One of the most frequent activities in dental practice is to detect early caries lesions or to provide treatment preventing more invasive therapies [8]. The International Caries Detection and Assessment System (ICDAS) was developed by an international team of caries researchers to integrate several new criteria systems into one standard system for caries detection and assessment [9]. A workshop was organized to discuss and reach consensus about definitions of the most common terms in cariology [10].…”
Section: Introductionmentioning
confidence: 99%
“…According to ICDAS criteria, there was a higher prevalence of non-cavitated enamel lesions in obese children (10.5%) compared to the non-obese children (1.9%), with significant differences between the groups ( p <0.001) 6. Non-cavitated enamel lesions could be better detected by ICDAS before progression of these lesions to cavitation 5. I presume that if Farsi et al1 employed ICDAS criteria in the methodology, the study results might be altered.…”
mentioning
confidence: 90%
“…Evaluation of the ICDAS platform has found that the system is practical; has content validity, correlational validity with histological examination of pits and fissures in extracted teeth; and discriminatory validity 4. Moreover, ICDAS represents a clinical scoring system that could be used in dental education, clinical practice, research, and epidemiology, and it provides a framework to support and enable personalized total DCs management for improved long-term health outcomes 5. Recently published evaluation of DCs using DMFT/dmft index and ICDAS in both obese and non- obese children has shown interesting results 6.…”
mentioning
confidence: 99%